1988
DOI: 10.1016/0022-5088(88)90332-3
|View full text |Cite
|
Sign up to set email alerts
|

Nb3Al formation in sputter-deposited Nb/Al multilayer samples

Abstract: The critical current density of powder metallurgy processed wires is determined in part by the extent of the A 15 phase formation in the vicinity of the Nb/ Al interface.A series of multi-layered samples was made to simulate the reactions in the P/M wires.Transmission electron microscopy was used to study the reactions between the multi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Figure 6 B uses the same colors of each data point to attribute the datum to a specific NMM structure (bcc/fcc, fcc/fcc, hcp/hcp, etc.) from the present study as well as the other previously identified studies from literature [ 17 , 18 , 19 , 20 , 52 , 63 , 65 , 66 , 67 , 68 , 69 ]. For a given subset of NMM structures (e.g., fcc/bcc), a more pronounced trend of decreasing normalized layer breakdown temperature with increasing surface energy mismatch is evident.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Figure 6 B uses the same colors of each data point to attribute the datum to a specific NMM structure (bcc/fcc, fcc/fcc, hcp/hcp, etc.) from the present study as well as the other previously identified studies from literature [ 17 , 18 , 19 , 20 , 52 , 63 , 65 , 66 , 67 , 68 , 69 ]. For a given subset of NMM structures (e.g., fcc/bcc), a more pronounced trend of decreasing normalized layer breakdown temperature with increasing surface energy mismatch is evident.…”
Section: Resultssupporting
confidence: 81%
“…Colors of the data points correspond to NMM alternating structure (e.g., bcc/fcc, fcc/bcc, etc.). from this study and other studies [ 17 , 18 , 19 , 20 , 52 , 63 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Figuresupporting
confidence: 69%
See 1 more Smart Citation